Assessing the Effect of Green Human Resource Leadership on Organizational Culture Change Toward Environmental Awareness and Sustainability Goals - Titis istiqomah; Endang Sarwiningsih Setyawulan (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study aims to explore the role of Green Human Resource Leadership (GHRL) in driving organizational culture change towards environmental awareness and sustainability goals. Employing a qualitative methodology through a systematic literature review (SLR), this research analyzes and synthesizes existing studies on GHRL, organizational culture, and sustainability. The data were collected from peer-reviewed journal articles, books, and conference papers, focusing on literature published in the last decade. The findings reveal that GHRL significantly influences organizational culture by embedding sustainability practices in recruitment, training, and performance management systems. Leaders who prioritize sustainability can create a culture of environmental responsibility, fostering employee engagement in green initiatives. However, the study also identifies challenges such as resistance to change and a lack of prioritization by top management, which hinder the full integration of GHRL practices. Additionally, the alignment of organizational culture with sustainability goals is essential for achieving long-term environmental performance and organizational success. The study concludes that GHRL plays a crucial role in driving cultural shifts toward sustainability, but overcoming barriers requires strong leadership commitment and clear communication. Further research is recommended to explore the specific mechanisms through which GHRL impacts sustainability outcomes and to investigate its influence across various industries and organizational contexts.